(untitled) (ModaPalavra e-periódico, 2012)
Considering the breadth and importance of color in various areas, this article aims to demonstrate the relevance of the study of color applied to the process that encompasses the generation of a product (from the product packaging, advertising to publicize the product). It aims to demonstrate the ability of color information through the analysis of stimuli, perception and syntax of the color, as well as through their use symbolic and linguistic transmission of messages and information, revealing the influence of psychodynamic factors in consumer choice and the importance of market research and analysis of trends in product design.